PERBANDINGAN PENCAMPURAN DAGING IKAN PATIN (Pangasius hipopthalmus) DENGAN IKAN GABUS (Channa striata) PADA KARAKTERISTIK SURIMI - Bobby Saputra; Desmelati Desmelati; Sumarto Sumarto (Berkala Perikanan Terubuk, 2016)
The purpose of this research was to evaluate the quality characteristic of surimi where made from a mixture of pangasius catfish and snakehead meat. Catfish and snakehead weighing range 800-1.000 gram/fish were obtained from a fish market in Pekanbaru. Catfish and snakehead meat was separated and blended. Five types of surimi were prepared from the two fish meat with a ratio of catfish and snakehead : 100% catfish meat, 100% snakehead meat, 75% catfish meat + 25% snakehead meat, 50% catfish meat + 50% snakehead meat and 25 % catfish meat + 75% snakehead meat. Surimi was leached in a fluid with 0,3% salt, temperature 5-10oC for 15 minutes, filtered, pressed then added 4% sucrosa, 4% sorbitol and 0,3% STTP. Surimi was analized for quality characteristics, gel strength (fold test and bite test), water holding capacity, pH and proximate. The research was designed using RAL and different between treatments were tested by Duncan test. The results showed surimi was prepared ​​from50% catfish meat+ 50% snakehead was the best treatment; the folding test value was 4,2 which was not cracked when folded in half circle; the bite test value was 7,2 strongly elasticity; water holding capacity 37,7%; pH 6,2; protein contant 17,7%; fat contant 0,9% and ash contant 2,1%.